Turkism in Slavic language - Kortabaeva, G. K. (Journal of Oriental Studies, 2016)
Turkism in Slavic language – words borrowed from Turkic languages, Russian, Old and Proto-Slavic languages in different historical periods. This article discusses Turkisms that are so ingrained in the language, that sometimes it is very diffi cult to determine. They are so entrenched in the language, which sometimes can be very diffi cult to determine. Help can only dictionaries, which describes in detail the meaning and origin of words. This article is devoted to the Turkic-Slavic language contact, which continue to be relevant to the present and adds a number of studies looking at the Turkic lexical items in the vocabulary of the Slavic languages, including Polish. Language of Turkic peoples have left many traces in various languages, including polyakskom.